QUALITY STANDARDIZATION OF LONGAN SEED EXTRACT (EUPHORIA LONGAN STEND) - RATNAH, ST.; SALASA, ALFRIDA MONICA (International Journal of Current Pharmaceutical Research, 2022)
Objective: Economic development in urban areas is a big attraction that causes urbanization so that the population increases. This has an impact on health, including skin health. One of the skin disorders is acne. Acne can be overcome with the use of traditional medicine. Longan Fruit Seed Extract contains phytochemical compounds that act as antibacterial and antioxidant. The purpose of this study was to obtain scientific data on the standardization of the quality of longan seed extract. Methods: Longan seeds were made simplicia, extracted by sokhletasi method and tested for standardization of extract quality. Results: The results of this study for specific parameters obtained extract identity, organoleptic test data form thick (sticky), glossy brown color, has a distinctive odor like longan flesh and sweet taste. The content of water-soluble compounds was 67.02±1.84, ethanol-soluble was 25.62±0.57. The total flavonoid content calculated as quercetin was 0.27±0.041. Non-specific parameters obtained data on water content 27.80 %±0.82, total ash content 1.58%±0.05, acid insoluble ash content 0.066 %±0.04, ALT 64x102 colonies/g, AKK 7x102 colonies/g, 0.0094 ppm Hg, 0.96 ppm As and 0.031 ppm Pb. Conclusion: Longan seed extract meets the requirements for standardization of extract quality.